Peningkatan Kualitas Lingkungan melalui Program Penghijauan dan Pengelolaan Sampah di Desa Sesaot: Implementasi KKN PMD UNRAM - Abdul Latip Rosyidin; Muhammad Chatim; Daiyan Rinjani Rachmawati; Nita Dianti; Cokorda Istri Widya Suari; Yulia Citrawati; Ida Ayu Putri Pradnya Utami; Sal Sabila Putri; Lalu Faesal Ahmad; Dian Anugrah Putri Pertiwi; Hasma Hasma (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
In Sesaot Village, Narmada Sub-district, West Lombok Regency, students from Mataram University are implementing the Community Services (KKN PMD). Through a number of initiatives such as cleaning riverbanks, planting trees, maintaining tourist trails, promoting waste management in the community, and providing training on the utilization of plantation products, the main objectives of this program are community economic empowerment and environmental quality improvement. These initiatives have successfully raised community awareness of the importance of protecting the environment and encouraged the conversion of plantation produce into high-quality and profitable goods. The program actively involves the community in all stages, from planning to evaluation, through the use of participatory methodologies. As a result, the environment has improved, the area has become more beautiful, and the empowerment of the community, especially the women who run MSMEs, is expected to contribute to the community. All of these developments are expected to have a long-term positive impact on the welfare of the village community.